Influencia de la estacionalidad sobre los ritmos forrajeros de Atta laevigata (Hymenoptera: Formicidae) en una sabana tropical - Farji Brener, Alejandro G (Universidad de Costa Rica, 1993)
In a tropical savanna (Venezuela) the foraging activity al eight colonies al the leaf-cutting ant Atta laevigala was measured (24 h perlods) in dry and rainy seasons. There was no deímed synchronization of diumal-noctumal foraging between nests. 'Ibis suggests That their foraging rhythms are not directly maintained by enviromnental factors. Intemal pbysiological rtythms such as nutritional requirements appear 10 be the basic cause al the changes in the noctumal/diumal foraging pattems.